A Unique Case of Intradural Communicating Branches between the Accessory Nerve and the Dorsal Roots of the Cervical Spinal Nerves - Şeker, Aşkın; Ceylan, Davut; Tatarlı, Necati; Abdullaev, Tuychiboy; Gülbar, Seda; Konya, Deniz; Bayri, Yasar; Keleş, Evren; Kılıç, Türker; Çavdar, Safiye (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objective The accessory nerve has cranial and spinal roots. The cranial roots emerge from the medulla, whereas the spinal roots arise from motor cells within the ventral horn of C1-C7 segments of the spinal cord. Communications have been described between the spinal accessory nerve rootlets and the dorsal rootlets of cervical spinal nerves. In the present case, we report a communication that has not been reported before and discuss the functional anatomy.Materials and Methods During the dissection of the craniovertebral junction of a 67-year-old formalin-fixed adult male cadaver, a connection between the spinal accessory nerve rootlets and the dorsal rootlets of the cervical spinal nerves was observed.Results A communication between the spinal rootlets of the accessory nerve and the dorsal roots of cervical spinal nerves was present on the right and left side. On the right, a communication between the accessory nerve spinal rootlet and the dorsal rootlet of the fourth cervical spinal nerve existed. On the left, there were two branches from the lowest accessory nerve spinal rootlet, one run ventrally and the other dorsally to the spinal rootlet and reached the dorsal root of third cervical spinal nerve. The dorsal root of C1 did not exist on either the right or the left side. Further, an unusual spinal accessory nerve formation was also observed.Discussion This case does not fit into any of the previously described classifications in the literature. Therefore, the different variations concerning the communications between the spinal rootlets of the accessory nerve and the cervical spinal nerves should be kept in mind during both surgical, especially radical neck dissections, and nonsurgical evaluations.
Keywords: variation; connections; accessory nerve; posterior root